Clinical characteristics of pancreatic and biliary tract cancers associated with Lynch syndrome. (9th November 2021) - Takamizawa, Shigemasa; Morizane, Chigusa; Tanabe, Noriko; Maruki, Yuta; Kondo, Shunsuke; Hijioka, Susumu; Ueno, Hideki; Sugano, Kokichi; Hiraoka, Nobuyoshi; Okusaka, Takuji
Abstract: Background/Purpose: Pancreatic and biliary tract cancers are one of the Lynch syndrome‐associated malignancies. There are few reports describing the patients' backgrounds and clinical characteristics. Methods: We retrospectively reviewed the medical records of patients with Lynch syndrome‐associated pancreatic or biliary tract malignant tumors at National Cancer Center Hospital between March 1992 and October 2019. Results: Fourteen patients were included. They had a history of multiple cancers and a family history of cancer. For the six patients with pancreatic malignant tumor, the median age was 63 years. The primary tumor site of 5/6 patients with pancreatic cancer was the body or tail. Only one patient had pancreatic head cancer. The median overall survival (OS) was 68 (range, 17‐198) months. For the eight patients with biliary tract malignant tumor, the median age was 65.5 years. The primary tumor site of 5/8 patients was the intrahepatic bile duct, whereas the primary site of 2/8 was the hilar bile duct. The median OS was 62 (range, 3‐183) months. Conclusions: This study brought out several observations on tumor location, late development, and favorable long‐term outcomes. Additional studies are needed to identify the characteristics. Abstract : Highlight Takamizawa and colleagues evaluated the backgrounds and clinical characteristics of patients with Lynch syndrome‐associated pancreatic or biliary tract cancers. The characteristic features include tumor location, late development, and favorable long‐term outcomes. An appropriate screening method for pancreatic or biliary tract cancers in patients with Lynch syndrome should be established.